Structural behaviour of thin-walled CHS-RHS T-joints: Experimental and numerical assessment. (August 2021) - Guerra, Messias; Pereira, Daniel; Neto, João Batista; Nunes, Gabriel; Sarmanho, Arlene; Lima, Luciano
Abstract: The design of tubular joints with slender cross-sections is currently limited by the validity ranges of established international design standards. Aiming to assess the structural behaviour of tubular joints characterised by thin-walled chord cross-sections, this paper initially reports, an experimental investigation into tubular T-joints consisted of CHS braces welded to thin-walled cold-formed RHS chords, which slenderness values were outside of the current design standard limits. The experimental programme was carried out on 12 cold-formed steel slender cross-section prototypes where the braces were subjected to axial compressive loading. The geometric parameters, including chord and brace thickness and brace diameter were varied. The connected chord face failure was the failure mode observed in all tests. The results of the experimental tests were thoroughly discussed. A second step was used to calibrate a numerical model that was the basis for a parametric analysis involving the most relevant parameters affecting the joint's behaviour. The obtained joint's strengths were compared with those forecasted by ISO 14346 developed for compact cross-sections modifying the chord stress function concerning the elastic cross-section modulus and effective cross-section area when slender cross-section chords are concerned. However, this approach leads to scattered predictions, roughly too conservative. Finally, this paper proposes an alternative design approach for the studied joints that are more accurate in predicting their strength when compared to the presented experimental and numerical results.